Collagen-based composite nanofiber membrane as well as preparation method and application thereof

By combining collagen with gel polysaccharide esterified derivatives to prepare composite nanofiber membranes, the fragility and low stability of collagen materials in wound dressings are solved, and higher mechanical properties and wound repair capabilities are achieved.

CN119564914AInactive Publication Date: 2025-03-07GUANGZHOU SYBETTER MEDICAL TECHNOLOGY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411700218.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing collagen materials have problems of fragility and low stability when used as wound dressings, affecting their role in promoting wound repair.

Method used

By combining collagen with gel polysaccharide esterified derivatives, composite nanofiber membranes are prepared, and the diameter and distribution of nanofibers are controlled by electrospinning technology to improve their mechanical properties and stability.

Benefits of technology

It significantly improves the mechanical stability and wound repair ability of collagen, can actively regulate the cytokine release of macrophages, promote wound healing, and exhibit excellent wound repair effects in in vivo experiments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119564914A_ABST
    Figure CN119564914A_ABST
Patent Text Reader

Abstract

The invention provides a collagen-based composite nanofiber membrane as well as a preparation method and application thereof. The nanofiber membrane comprises a gel polysaccharide esterification derivative and collagen. The composite nanofiber membrane can simulate a natural extracellular medium, can actively adjust release of cytokines of macrophages so as to accelerate wound healing, is a wound dressing with excellent performance, and can rapidly repair wounds. Meanwhile, the composite nanofiber membrane is small in aperture, high in porosity and large in nanofiber specific surface area, and cell proliferation and migration can be promoted. Moreover, the composite nanofiber membrane has better tensile strength, so that the composite nanofiber membrane has better mechanical property when being used as a wound dressing or a medical implant, and mechanical injury can be prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of biomedical materials, and specifically relates to a collagen-based composite nanofiber membrane and a preparation method and application thereof. Background Art

[0002] As the largest organ in the human body, the skin requires external assistance to complete self-repair when a large area is damaged. Wound dressings have become a powerful tool to promote the repair and regeneration of skin defects. These dressings provide a three-dimensional structure for cell-to-cell interactions, mimic the natural extracellular matrix (ECM), and guide the spatiotemporal complex multicellular process of tissue formation and regeneration. Collagen, chitosan, alginate, gelatin, and polyurethane are widely used to prepare various types of skin wound repair dressings. These new wound dressings have shown excellent performance in promoting wound repair to a certain extent.

[0003] The repair process of injured skin is extremely complex, involving inflammation, cell proliferation, re-epithelialization and remodeling. Macrophages and fibroblasts play a vital role in these processes. During the proliferation phase, proliferating fibroblasts produce collagen and migrate to the wound site to form new ECM. In the early short-term inflammatory phase, macrophages present a classic M1 phenotype, highly express proinflammatory cytokines such as interleukin-1β (IL-1β), interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α), and have functions such as antigen presentation and clearance of cells and dead tissues. In the proliferation phase, macrophages present an M2 phenotype, highly express interleukin-10 (IL-10), transforming growth factor β (TGFβ) and chemokine CCL18. These cytokines can stimulate collagen production, fibroblast proliferation, and indirectly or directly stimulate the proliferation of connective tissue, epithelial tissue and endothelial tissue.

[0004] In view of this, designing a wound dressing that can actively regulate cell function, especially macrophage function, is of great significance for the further development of skin tissue engineering. Summary of the invention

[0005] In order to solve the problems and deficiencies in the prior art, the present invention provides a composite nanofiber membrane based on collagen, and a preparation method and application thereof. The composite nanofiber membrane can simulate natural extracellular media, and can actively regulate the release of cytokines from macrophages to accelerate wound healing. It is a wound dressing with excellent performance and can quickly repair wounds. At the same time, the composite nanofiber membrane has a small pore size, high porosity, and a large specific surface area of ​​nanofibers, which can promote cell proliferation and migration. Moreover, the composite nanofiber membrane has good tensile strength, so that it has good mechanical properties as a wound dressing or medical implant, which can ensure the prevention of mechanical damage.

[0006] According to a first aspect of the present invention, there is provided a collagen-based composite nanofiber membrane comprising a curdlan esterified derivative and collagen.

[0007] Collagen fibers are an important component of the extracellular matrix, ensuring the three-dimensional spatial structure and biological properties of the extracellular matrix. In the biomedical field, collagen is the most important and widely used natural polymer. Clinically, it has the ability to stop bleeding and repair wounds, so it is often used to prepare artificial dressings and artificial skin. For example, type I and type III collagen can stimulate the production of anti-inflammatory cytokines such as IL-10 and TGF-β, which helps maintain immune homeostasis. However, collagen materials usually have problems of fragility and low stability. The fragility and low stability of collagen will cause its role as a wound dressing to promote wound repair to be significantly reduced, which is not conducive to wound repair.

[0008] The present invention utilizes collagen and a gellan esterified derivative to prepare a composite nanofiber membrane, which effectively improves its mechanical properties and stability as a wound dressing, thereby greatly promoting the role of collagen in wound repair, especially improving its regulatory effect on macrophages and fibroblasts by releasing anti-inflammatory / pro-inflammatory molecules, effectively reducing unnecessary immune stimulation and promoting beneficial immune responses, maintaining a better balance in the local immune microenvironment of the wound, and creating more favorable conditions for wound healing.

[0009] Specifically, collagen itself can stimulate the production of anti-inflammatory / pro-inflammatory molecular cytokines, thereby regulating the interaction and dynamic balance between macrophages and fibroblasts, and achieving effective wound healing and tissue regeneration. As mentioned above, collagen itself has the problem of fragility and low stability (low mechanical strength), which will affect its role in wound repair. Therefore, the present invention introduces a gelatin esterified derivative. It has been verified by relevant experiments that the addition of a gelatin esterified derivative greatly improves the tensile strength of the collagen product (composite nanofiber membrane), that is, effectively improves the mechanical stability of collagen, thereby greatly improving the wound repair ability of collagen. This is because, similar to curdlan (Curdlan, also known as curdlan, is a water-insoluble linear β-1,3-glucan and a high molecular weight polymer of glucose. Curdlan is composed of β-(1,3) linked glucose residues and forms an elastic gel after heating in an aqueous suspension. It was originally extracted from the fermentation species of Alcaligenes faecalis variant myxogenes.), curdlan esterified derivatives also have good strength, elasticity and thermal stability, so they can significantly improve the mechanical strength of collagen products and promote the wound repair performance of collagen. And the curdlan esterified derivatives have a triple helical conformation similar to collagen. In addition to showing high mechanical properties, they also show high immunostimulatory ability. Curdlan esterified derivatives can bind to the dectin-1 receptor of macrophages to enhance their phagocytic activity against wound debris and pathogens. Moreover, the esterified derivative of gellan has high hydrophilicity, which is conducive to the preparation of highly hydrophilic composite nanofiber membranes, which are beneficial to the absorption of tissue fluid exuded from the wound, while retaining the absorbed moisture in the dressing, thereby forming a moist environment on the wound surface. Compared with the traditional dry healing environment, this moist environment is more conducive to wound healing.

[0010] Moreover, compared with wound dressings such as gauze, hydrogel and sponge, the composite nanofiber membrane provided by the present invention has many advantages, such as small pore size, large specific surface area, high porosity, which can promote cell proliferation and migration and is more conducive to wound repair.

[0011] At the same time, it should be noted that the use of gelatin esterified derivatives is more conducive to dissolving in organic solvents to obtain a homogeneous solution, which is conducive to further processing and obtaining uniform and high-quality composite nanofiber membranes. Preferably, the mass ratio of gelatin esterified derivatives and collagen is 3 to 9: 1 to 7. At this mass ratio, the gelatin esterified derivatives and collagen can give full play to their own effects and will not significantly affect the role of each other, which is conducive to improving the overall performance of the obtained nanofiber membrane and optimizing the role of the composite nanofiber membrane in repairing wounds. And the gelatin esterified derivative is similar to gelatin. After electrospinning with collagen, it does not gel and is in a nanofiber state.

[0012] Preferably, the mass ratio of the curdlan esterified derivative to the collagen is 5-8:2-5.

[0013] Preferably, in the composite nanofiber membrane, the average diameter of the nanofibers is 20 to 500 nm. Controlling the average diameter of the nanofibers in the composite nanofiber membrane within the above-mentioned smaller range can ensure that the composite nanofiber membrane formed by the nanofibers has a higher porosity, while increasing the specific surface area of ​​the nanofibers, thereby promoting cell proliferation and migration as well as hydrophilicity, and improving the wound repair ability of the composite nanofiber membrane. At the same time, a smaller average diameter means that the pore size formed between the nanofibers is smaller, and a smaller pore size means that the fibers are more tightly bound and the interaction force is enhanced, which helps to improve the overall strength of the composite nanofiber membrane. When subjected to external forces, relative displacement and deformation are not easy to occur between the fibers, so that the composite nanofiber membrane can withstand greater loads such as tension and pressure.

[0014] Preferably, in the composite nanofiber membrane, the average diameter of the nanofibers is 60 to 250 nm.

[0015] Preferably, in the composite nanofiber membrane, the esterified derivative of curdlan includes ester-containing fatty acid curdlan; the ester-containing fatty acid curdlan includes at least one of acetate curdlan, propionate curdlan, butyrate curdlan, valerate curdlan, and caproate curdlan; collagen includes at least one of type I collagen, type II collagen, type III collagen, type XVII collagen, and recombinant humanized collagen. Preferably, acetate curdlan, propionate curdlan, butyrate curdlan, valerate curdlan, and caproate curdlan are obtained by reacting acetic acid, propionic acid, butyric acid, valeric acid, and caproic acid with curdlan, respectively. It should be noted here that the esterified derivative of curdlan is obtained by reacting curdlan with fatty acids, and the fatty acids include fatty acids with no more than 12 carbon atoms. Preferably, the fatty acids include at least one of acetic acid, propionic acid, butyric acid, valeric acid, and caproic acid.

[0016] Preferably, the collagen includes type I collagen. The composite nanofiber membrane formed by type I collagen and the esterified derivative of curdlan has a better synergistic effect with each other, which is beneficial to further promote the mechanical stability and wound repair ability of the composite nanofiber membrane.

[0017] According to a second aspect of the present invention, a method for preparing the composite nanofiber membrane is provided, comprising the following steps: S1. dissolving a curdlan esterified derivative and collagen in an organic solvent to obtain an electrospinning solution; S2. forming a nanofiber membrane by electrospinning the electrospinning solution. The electrospinning method is advantageous for controlling the nanofibers in the composite nanofiber membrane to have a suitable diameter, and can also improve the uniformity of the diameter distribution of the nanofibers, which is advantageous for improving the overall performance of the composite nanofiber membrane.

[0018] Preferably, in S1, the mass volume ratio of the total mass of the esterified derivative of gelatin and collagen to the organic solvent is 1 to 6%; the organic solvent includes hexafluoroisopropanol. An appropriate solute mass fraction helps to obtain uniform nanofibers. If the mass fraction is too low, the solution conductivity is poor, the jet is unstable, and beaded fibers are easily produced; if the mass fraction is too high, the solution viscosity is too high, which may lead to uneven fiber thickness. Therefore, the mass volume ratio of the total mass of the esterified derivative of gelatin and collagen to the organic solvent is controlled within the above range, which is a relatively moderate mass fraction. At this time, the viscosity and conductivity of the solution are well balanced, and the jet can be stably stretched from the nozzle to the receiving device, which is conducive to the formation of continuous and uniform fibers, ensuring that the final composite nanofiber membrane has better mechanical stability and optimizes the wound repair performance of the composite nanofiber membrane.

[0019] Preferably, the mass volume ratio of the total mass of the curdlan esterified derivative and collagen to the organic solvent is 3-4%.

[0020] Preferably, in S1, during the electrospinning process, the flow rate of the syringe pump is 1-3 mL / h, and the electrospinning collection distance, speed and DC voltage are 10-30 cm, 1300-1800 rpm / s and 15-40 kV, respectively.

[0021] According to the third aspect of the present invention, there is provided an application of the composite nanofiber membrane or the composite nanofiber membrane prepared by the preparation method of the composite nanofiber membrane in the preparation of wound dressings or medical implants. The composite nanofiber membrane provided by the present invention is used as a wound dressing to simulate ECM and actively regulate the release of cytokines of macrophages to accelerate wound healing, and has a higher wound repair ability. At the same time, the composite nanofiber membrane has good mechanical strength and hydrophilicity, which can further promote its ability to repair wounds. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 (a) is the Fourier transform infrared spectrum of curdlan; (b) is the Fourier transform infrared spectrum of CDA.

[0023] Figure 2 Representative SEM morphologies (A), nanofiber diameter distribution (B) and average nanofiber diameter (C) of different nanofiber membranes or composite nanofiber membranes; (a) represents CDANM, (b) represents CDAColNM2, and (c) represents CDAColNM5.

[0024] Figure 3 Water contact angle (A) and swelling ratio (B) of different nanofiber membranes or composite nanofiber membranes; (a) represents CDANM, (b) represents CDAColNM2, and (c) represents CDAColNM5.

[0025] Figure 4 Stress-strain curves (A), tensile strength (B), and elongation at break (C) of different nanofiber membranes or composite nanofiber membranes, ***P<0.001, **P<0.01, *P<0.05; (a) represents CDANM, (b) represents CDAColNM2, and (c) represents CDAColNM5.

[0026] Figure 5 Relative cell viability of NIH3T3 and RAW264.7 cultured on nanofiber membranes or composite nanofiber membranes for 1 day, 3 days and 7 days (A); SEM images of NIH3T3 and RAW264.7 cultured on nanofiber membranes or composite nanofiber membranes for 3 days (B); laser confocal images of NIH3T3 and RAW264.7 cultured on nanofiber membranes or composite nanofiber membranes for 3 days (C); cells were stained with rhodamine Phalloidin (red) for f-actin cytoskeleton, and DAPI for nuclei (blue); (a) represents CDANM, (b) represents CDAColNM2, and (c) represents CDAColNM5.

[0027] Figure 6 RAW264.7 cells were cultured in PBS (a), CDANM (b) and CDAColNM5 (c) for 1, 3, 7 and 14 days, respectively, to induce the expression of cytokines IL-6 (A), IL-10 (B) and TGF-β (C); and the NO concentrations of RAW264.7 cells were treated with different samples for 24 hours (D); (a) represents CDANM, (b) represents CDAColNM2, and (c) represents CDAColNM5. Compared with the control group, *p<0.05.

[0028] Figure 7Representative images of skin wounds treated with CDANM, CDAColNM5 and collagen at 0, 3, 7 and 14 days (A) Quantitative analysis of the remaining wound area of ​​all groups (B). ****p<0.0001 compared with the blank group.

[0029] Figure 8 Representative H&E (A) and Masson (B) staining images of regenerated skin tissue at 3, 7, 14, and 21 days; scale bar: 100 μm; yellow and green arrows represent inflammasomes and epithelialization. DETAILED DESCRIPTION

[0030] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only embodiments of a part of the present invention, rather than all embodiments.

[0031] The materials used in the specific embodiments and comparative examples of the present invention are as follows: Curdlan (molecular weight: 6×10 Da) was purchased from Wako Pure Chemical Industries, Ltd. (Osaka, Japan). Collagen was a high-purity, high-transparency type I collagen with a triple helical structure and no immunogenicity extracted from animal Achilles tendon tissue (Guangzhou, China). Trifluoroacetic anhydride, acetic acid, and hexafluoroisopropanol were purchased from Sigma-Aldrich (St. Louis, USA). Dulbecco's modified Eagle's medium (DMEM), penicillin / streptomycin solution, and fetal bovine serum (FBS) were purchased from Gibco (New York, USA). Phosphate buffered saline (PBS) and other detection kits were purchased from Jiangsu KeyGen Biotech Co., Ltd. (Nanjing, China). Commercially available reagents or materials were used directly without further purification.

[0032] The esterified curdlan derivative used in the present invention can be synthesized with reference to the document "Carbohydrate Polymers, 2014, Volume 103, Pages 427-433.", which can be briefly summarized as follows: Predried curdlan (0.5 g) is dispersed in acetic acid / trifluoroacetic anhydride (10 mL / 20 mL). The reaction mixture is further stirred at 50° C. for 1 hour. After cooling to room temperature, the mixture is slowly poured into a sodium bicarbonate aqueous solution (200 mL). Finally, the precipitate is centrifuged, washed with water until neutral, and freeze-dried to obtain a white solid product, a curdlan esterified derivative (CDA).

[0033] Examples and Comparative Examples

[0034] The present invention provides two embodiments and one comparative example, wherein in comparative example 1, embodiment 1 and embodiment 2, the mass ratios of CDA to collagen (collagen I) are 10:0, 8:2 and 5:5 respectively. The steps of preparing the nanofiber membrane or the composite nanofiber membrane are as follows:

[0035] S1. Dissolving CDA and collagen (collagen I) in hexafluoroisopropanol (HFIP) to obtain an electrospinning solution; the total mass of CDA and collagen (collagen I) and the mass concentration of hexafluoroisopropanol are 3.5% (w / v);

[0036] S2. The electrospinning solution was loaded into a 20 mL syringe (equipped with a 21-gauge needle) and driven by a syringe pump at a flow rate of 2 mL / h. The electrospinning collection distance, speed, and DC voltage were set to 15 cm, 1500 rpm / s, and 20 kV, respectively; the resulting nanofiber membrane was dried under vacuum overnight to remove residual solvent.

[0037] Test analysis

[0038] 1. Structure and performance characterization

[0039] (1) Infrared characterization

[0040] The prepared CDA and raw material curd polysaccharide were characterized by infrared spectroscopy. Specifically, a Fourier transform infrared spectrometer (Nicolas 6700, USA) was used to obtain FT-IR data in the range of 400 to 4000 cm-1 at a resolution of 4 cm-1.

[0041] Test results such as Figure 1 As shown, Figure 1 FT-IR spectra of curdlan and CDA. Figure 1 It can be seen that CDA contains all the peaks of curdlan, except for three new peaks at 1751cm-1, 1374cm-1 and 1228cm-1, which are attributed to -C=O stretching vibration, -CH bending vibration and -CO stretching vibration, respectively. The characteristic peak at 1751cm-1 indicates that the hydroxyl group is replaced by an ethyl ester group. Figure 1 The FT-IR results confirmed the successful synthesis of CDA.

[0042] (2) Morphological characterization

[0043] The nanofiber membrane or composite nanofiber membrane prepared in the above examples and comparative examples was characterized by scanning electron microscopy (Philips XL-30ESEM, Netherlands) to examine the morphology of the nanofiber membrane or composite nanofiber membrane. Before observation, all sample surfaces were sprayed with gold. ImageJ software was used to measure the diameter of the nanofibers in the nanofiber membrane or composite nanofiber membrane in the scanning electron microscope image.

[0044] The surface physical morphology of skin dressings has a significant impact on cell proliferation and adhesion. The optimal skin dressing structure can best simulate the structure and function of the extracellular matrix. Figure 2 A shows the scanning electron microscope images of CDANM (Comparative Example 1), CDAColNM2 (Example 1) and CDAColNM5 (Example 2). It can be found that all membranes have smooth surfaces without beads, forming interconnected pores. Figure 2 B-2C shows that the average diameter of CDANM, CDAColNM2 and CDAColNM5 is measured as 159 ± 63nm, 113 ± 34nm and 105 ± 32nm respectively. That is, along with the adding of collagen, the diameter of nanofiber has the trend of reducing. Extracellular matrix is ​​mainly composed of various nano fiber structures, such as collagen fiber, reticular fiber and elastic fiber. As the main component of extracellular matrix, the diameter of collagen fiber is generally about 50 to 500nm, specifically depends on specific organization. Therefore, the composite nano fiber membrane prepared by the present invention can simulate the structure of extracellular matrix to a certain extent.

[0045] (3) Characterization of water contact angle and swelling rate

[0046] The nanofiber membrane or composite nanofiber membrane prepared in the above examples and comparative examples was characterized by water contact angle and swelling rate. Specifically, an optical contact angle meter (OCA25 from Dataphysics, Germany) was used to measure the water contact angle. When doing the swelling experiment, the dry nanofiber membrane (M) was immersed in PBS (10 mL) at 37°C and taken out after 24 hours; the PBS remaining on the surface of the membrane was carefully absorbed with filter paper, and the weight of the swollen nanofiber membrane was measured as M; the swelling rate (%) was calculated using the following formula:

[0047]

[0048] The contact angle of different nanofiber membranes or composite nanofiber membranes is measured over time to reflect their hydrophilicity. The ideal wound dressing material should have the ability to absorb wound exudate while maintaining the ability to cover the wound. Figure 3 As shown in A, the water contact angles (contact 60 seconds) of CDANM, CDAColNM2 and CDAColNM5 are 44°, 19° and 0° respectively. It is generally believed that materials with a contact angle less than 90° are hydrophilic materials. Therefore, all nanofiber membranes or composite nanofiber membranes prepared by the present invention can be regarded as hydrophilic materials, and hydrophilicity increases with the increase of collagen content.

[0049] The formation of wounds is always accompanied by the production of exudate, which will affect the speed of wound repair. Therefore, skin dressings need to maintain effective exudate absorption activity. Figure 3 As shown in Figure B, the swelling rates of CDANM, CDAColNM2 and CDAColNM5 were recorded as 350.8%+7.6%, 450.3%+25.6% and 540.8%+83%, respectively. This trend is consistent with the contact angle results. This means that the composite nanofiber membrane provided by the present invention has a higher wound exudate absorption capacity, which is beneficial to promote wound repair.

[0050] (4) Mechanical properties characterization

[0051] The mechanical properties of the nanofiber membranes or composite nanofiber membranes prepared in the above examples and comparative examples were characterized, specifically using a universal testing machine (Instron, USA) to measure the mechanical properties of the nanofiber membranes (width 10 mm, length 40 mm, thickness 0.2 mm) at a tensile rate of 10 mm / min. The tensile strength and elongation at break were calculated from the obtained tensile stress-strain curves.

[0052] Excellent wound dressings require excellent mechanical properties to maintain integrity during implantation and replacement. Figure 4 As shown, the ultimate tensile strength of CDANM, CDAColNM2 and CDAColNM5 was measured as 2.37 ± 0.18MPa, 2.78 ± 0.19MPa, and 3.42 ± 0.33MPa, respectively. The elongation at break of CDANM, CDAColNM2 and CDAColNM5 was 39.64%, 25.57% and 9.59%, respectively. According to literature reports, collagen has the structural characteristics of high tensile strength and low ductility. Therefore, with the increase of collagen content, tensile strength increases and elongation at break decreases. As a wound dressing, relatively high strength can ensure the prevention of mechanical damage. The results show that CDA / collagen nanofiber membrane has good mechanical properties as a wound dressing, and by comparing the above embodiments with the comparative examples, it can also be seen that compared with pure CDA material, the composite nanofiber membrane prepared by CDA / collagen composite material has higher mechanical properties and has more performance advantages as a wound dressing.

[0053] It should be noted that all the above data are expressed as mean ± standard deviation (SD). One-way ANOVA was used to evaluate statistically significant differences (p < 0.05). SPSS19.0 was used for statistical analysis. Each experiment was repeated at least three times independently.

[0054] 2. Characterization of cell proliferation and adhesion

[0055] (1) Cell proliferation assay

[0056] The nanofiber membranes prepared in the above examples and comparative examples were rinsed three times with culture medium (DMEM), and then RAW264.7 (1×10 cells per well) or NIH3T3 (5×10 cells per well) cells were inoculated on the nanofiber or composite nanofiber membrane scaffolds and cultured at 37°C, 5% CO for 1, 3 or 7 days. Then, the cell viability was detected using a CCK-8 kit. The absorbance (450nm) was determined using a microplate reader. Cell viability (%) was calculated using the formula Ah / Ab×100%, where Ah represents the absorbance of the experimental cells and Ab represents the absorbance of the blank group cells.

[0057] Good cell compatibility is a prerequisite for further application of wound dressings. Therefore, cell compatibility was evaluated by viability assays using NIH3T3 and RAW264.7 cells on different membranes. Figure 5 As shown in A, the number of NIH3T3 and RAW264.7 cells increased with incubation time. The increase in collagen content was associated with enhanced cell proliferation. On day 7, the optical density (OD) values ​​of NIH3T3 in CDANM, CDAColNM2, and CDAColNM5 were 1.13, 1.20, and 1.30, respectively. Similarly, the OD values ​​of RAW264.7 on day 7 in CDANM, CDAColNM2, and CDAColNM5 were 0.88, 1.13, and 1.35, respectively. The above results indicate that the composite nanofiber membrane with the addition of collagen promoted the proliferation of NIH3T3 and RAW264.7 cells.

[0058] (2) Cell adhesion and growth patterns

[0059] The adhesion morphology and growth pattern of cells were observed by scanning electron microscopy (SEM) and confocal laser scanning microscopy (CLSM). After NIH3T3 and RAW264.7 cells were inoculated on nanofiber membranes or composite nanofiber membranes for 3 days, the pretreated cells were fixed with 4% paraformaldehyde and rinsed three times with PBS. Subsequently, the membranes inoculated with cells were dehydrated in different gradients of ethanol and air-dried. Finally, the samples were observed under a scanning electron microscope.

[0060] For confocal microscopy analysis, NIH3T3 and RAW264.7 cells were seeded on nanofiber membranes or composite nanofiber membranes for 3 and 14 days, respectively. Then, the pretreated cells were rinsed with PBS, fixed with 4% paraformaldehyde for 10 minutes, and rinsed three times with PBS. Subsequently, the samples were treated in 0.1% Triton X-100 in PBS for 5 minutes and then rinsed with PBS. The samples were then incubated in rhodamine phalloidin in the dark for 30 minutes and counterstained with DAPI (4',6-diamidino-2-phenylindole). Finally, the samples were observed under a confocal laser scanning microscope.

[0061] The results are as follows Figure 5 As shown in B, NIH3T3 cells adhered and spread on the surfaces of CDAColNM2 and CDAColNM5, showing a typical spindle-shaped cell morphology, while the cell morphology on CDANM was round and not stretched. At the same time, the number of NIH3T3 cells on CDAColNM5 was higher than that on other materials. Similarly, RAW264.7 cells also showed a similar trend, with more cells on CDAColNM5. This result is consistent with the cytotoxicity test, indicating that cell proliferation and adhesion on CDAColNM2 and CDAColNM5 are significantly better than CDANM.

[0062] Confocal microscopy was also used to image cells incubated on the membrane. Rhodamine-phalloidin was used to stain the actin cytoskeleton of the cells for fluorescence imaging. Figure 5 As shown in the confocal micrographs in C, after 3 days of incubation, NIH3T3 cells were tightly adhered to CDAColNM2 and CDAColNM5, and their actin cytoskeleton was well developed, in contrast to the situation on CDANM. After 14 days of incubation, RAW264.7 cells on CDAColNM2 and CDAColNM5 were extensively connected to each other compared with the situation on CDANM. Therefore, the above results indicate that CDA / collagen composite nanofibrous membrane promotes cell proliferation and adhesion. In addition, the above results also prove that CDA / ColNM2 and CDA / ColNM5 have better cell compatibility in further wound repair.

[0063] 3. Real-time quantitative polymerase chain reaction (RT-qPCR) analysis and nitric oxide (NO) determination

[0064] (1) Real-time quantitative polymerase chain reaction (RT-qPCR) analysis

[0065] During skin repair, macrophages overexpress interleukin-6 (IL-6) to induce phagocytosis during the inflammatory phase (1-3 days after injury) and overexpress interleukin-10 (IL-10) and transforming growth factor-β (TGF-β) to promote collagen production during the proliferative phase (3-9 days after injury). In order to promote wound repair, macrophages should be induced to secrete appropriate inflammatory cytokines during the inflammatory phase and anti-inflammatory factors and growth factors during the late proliferative phase to promote cell proliferation and collagen production.

[0066] Therefore, this experiment used fluorescent quantitative polymerase chain reaction (PCR) to detect the concentrations of cytokines interleukin-6 (IL-6), interleukin-10 (IL-10) and transforming growth factor-β (TGF-β) in RAW264.7 cells (after co-culture with nanofiber membranes for 1, 3, 7 and 14 days), that is, to detect the production of proinflammatory cytokines in RAW264.7 cells to evaluate the proinflammatory activity of nanofiber membranes or composite nanofiber membranes.

[0067] The specific steps of the test are as follows: 1.5 mL of culture medium and RAW264.7 cells (8×10 cells per well) were inoculated in a 24-well plate (with nanofiber membranes or composite nanofiber membranes of each comparative example and embodiment at the bottom), and cultured at 37°C in a humidified environment containing 5% CO for 1 day, 3 days, 7 days and 14 days. At the predetermined time, the culture supernatant was collected and centrifuged at 5000 rpm for 10 minutes. The expression levels of pro-inflammatory and anti-inflammatory factors were detected using RT-qPCR according to the manufacturer's instructions (n=4).

[0068] Test results such as Figure 6 As shown in A to C, CDAColNM5 promoted the secretion of interleukin-6 (IL-6) factor by macrophages from days 1 to 3, and promoted the secretion of interleukin-10 (IL-10) and transforming growth factor-β (TGF-β) from days 3 to 7. However, CDANM only stimulated the secretion of interleukin-6 (IL-6) from days 1 to 3, and did not affect the secretion of interleukin-10 (IL-10) or transforming growth factor-β (TGF-β). The above results show that CDANM plays an important role in promoting macrophages to differentiate into M1 type and secrete interleukin-6 (IL-6) within 1-3 days. However, from days 3 to 7, the stimulating effect of CDANM weakened, and the collagen in CDAColNM5 stimulated macrophages to differentiate into M2 type and secrete interleukin-10 (IL-10) and transforming growth factor-β (TGF-β). This indicates that the combined action of CDA and collagen can further enhance the differentiation of macrophages and the secretion of interleukin-10 and transforming growth factor-β (TGF-β), thereby significantly improving the wound repair effect of the wound dressing.

[0069] (2) Nitric oxide (NO) determination

[0070] The specific steps for the determination of nitric oxide (NO) are as follows: 1.5 mL of culture medium and RAW264.7 cells (7×10 cells per well) were inoculated in a 24-well plate (with nanofiber membranes or composite nanofiber membranes of various comparative examples and embodiments at the bottom), and cultured for 3 days at 37°C in a humidified environment containing 5% CO. At a predetermined time, the culture supernatant was collected and centrifuged at 5000 rpm for 10 minutes. A nitric oxide detection kit (Biyuntian) was used to quantitatively determine the nitric oxide in the cell culture supernatant. Lipopolysaccharide (LPS) and PBS were used as positive control group and negative control group, respectively (n=3).

[0071] Test results such as Figure 6 As shown in Figure D, the concentrations of nitric oxide in CDANM, CDAColNM2, and CDAColNM5 were 5, 4, and 3 times that of the negative control group, respectively. This indicates that CDA can stimulate RAW264.7 cells to produce nitric oxide to a certain extent, and the stimulation weakens with the increase of collagen content. Therefore, CDAColNM5 combines the properties of CDA and collagen in regulating macrophage cytokine secretion, thereby effectively promoting skin wound repair. Compared with pure CDANM, CDAColNM5 may better regulate macrophage cytokine secretion and reduce nitric oxide production.

[0072] It should be noted that all the above data are expressed as mean ± standard deviation (SD). One-way ANOVA was used to evaluate statistically significant differences (p < 0.05). SPSS19.0 was used for statistical analysis. Each experiment was repeated at least three times independently.

[0073] 4. In vivo wound healing assessment

[0074] To evaluate the wound healing effect of CDAColNM5, commercially available collagen dressings and untreated wounds were used as positive and negative controls, respectively.

[0075] This experiment was an animal experiment, and the animal experiment was conducted in accordance with the Guide for the Care and Use of Laboratory Animals of the National Research Council of the United States. The animal experiment was approved by the Animal Care and Experimentation Committee of Jinan University. Male Kunming mice (6-8 weeks) were weighed (about 20 g) and randomly divided into an untreated group (control group), a CDA / collagen 10:0 group, a CDA / collagen 5:5 group, and a commercially available collagen dressing (Guangzhou, China) group (n=5). The mice were anesthetized and shaved by intraperitoneal injection of 8% chloral hydrate (0.4 mg / g body weight). A 10 mm × 10 mm full-thickness incision was prepared on the back of each mouse by excision and disinfected with 75% ethanol. A sterile 12 mm × 12 mm wound dressing was laid flat and sutured to each wound. The wounds were photographed at different days after surgery.

[0076] The photo results are as follows Figure 7 As shown, on days 3 and 7, the untreated group and the group treated with CDANM alone had stronger inflammatory responses than the groups treated with CDAColNM5 or collagen alone; the inflammatory wound exudate completely penetrated the CDANM. By day 14, scabs appeared in the untreated group, while the remaining wound area in the group using collagen-containing materials was significantly smaller than that in the group without collagen. The percentages of remaining wound area in the blank control group, CDANM group, CDAColNM5 group, and collagen group were 50.6±5.9%, 41.6±7.5%, 7.5±2.4%, and 11.1±3.8%, respectively. On day 14, the wounds were still not completely healed except in the group containing collagen, while the untreated group had large scabs. These results indicate that both CDA and collagen as functional components of wound dressings show the effect of promoting repair, and the combination of these two components exerts the best promotion effect on wound repair. It should be noted that all the above data are expressed as mean ± standard deviation (SD). One-way ANOVA was used to evaluate statistically significant differences (p < 0.05). Statistical analysis was performed using SPSS 19.0. Each experiment was repeated at least three times independently.

[0077] Further, at specific time points, rats were killed by intraperitoneal injection of an overdose of chloral hydrate. The tissues around the wound were collected, fixed with 4% paraformaldehyde, and embedded in paraffin. Continuous sections were made perpendicular to the wound surface using a microtome to obtain tissue sections with a thickness of 8 μm. The sections were stained with hematoxylin-eosin (H&E) and Masson's trichrome, observed and photographed under a microscope. ImageJ was used to quantify the different color pixel values ​​of each image. The collagen index (CI) for each pixel was calculated using the following formula: (B / G) / (2R+B+G) (where B, G, and R represent blue, green, and red pixel values, respectively). The index is roughly linear with the collagen content.

[0078] like Figure 8As shown in A, hematoxylin-eosin (H&E) staining was used to evaluate the dynamic changes of inflammatory response and epidermal thickness. On the 3rd day, inflammation was observed in all groups (as shown by the yellow arrow in the figure), and the untreated group had more severe inflammation than the other groups. On the 7th day, except for the untreated group, the inflammatory response of other groups was significantly reduced. As shown by the green arrow in the figure, epithelium began to form at the edge of the wound in the CDAColNM5 group and the collagen group. On the 14th day, the inflammation in the untreated group subsided, and the granulation tissue in the other three groups thickened and the epidermis was fully formed. Our results show that the repair-promoting effect of CDAColNM5 is better than that of the CDANM group and the control group, and it achieves similar repair effects as commercially available collagen dressings.

[0079] like Figure 8 As shown in Figure B, Masson trichrome staining was used to evaluate the dynamic changes of collagen during wound repair. On the 3rd day, the level of collagen deposition in all groups was low, but by the 7th day, all groups had increased, and the total amount in the CDAColNM5 group was higher and accompanied by angiogenesis. On the 14th day, CDAColNM5 showed that collagen was evenly distributed, tightly aggregated and extended in parallel, accompanied by obvious papillary follicle structure, which was very similar to the normal skin structure. The reticular dermis of the CDANM group and the untreated group showed densely arranged collagen fibers near the epidermis, without the specific direction characteristics of scar tissue. Therefore, CDAColNM5 showed potential in promoting wound repair by enhancing cell adhesion, regulating macrophage inflammatory response and accelerating orderly collagen deposition. That is, the above results show that the combination of CDA and collagen can further promote the regeneration of collagen and is more conducive to promoting wound healing.

[0080] In summary, in the present invention, a multifunctional composite nanofiber membrane (CDA+collagen) with excellent physicochemical properties and biological activity was prepared by mixing and electrospinning technology. In in vitro experiments, it was found that the composite nanofiber membrane provided by the present invention can induce macrophages to release pro-inflammatory and pro-regenerative cytokines, such as interleukin-6 (IL-6), interleukin-10 (IL-10) and transforming growth factor-β (TGF-β). In vivo experiments have shown that the composite nanofiber membrane provided by the present invention can effectively promote wound repair by regulating macrophage inflammatory response, promoting re-epithelialization and promoting collagen deposition. That is, the composite nanofiber membrane provided by the present invention is a potential candidate material that can accelerate wound repair.

[0081] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.

Claims

1. A composite nanofiber membrane based on collagen, characterized in that: Including gellan ester derivatives and collagen.

2. The collagen-based composite nanofiber membrane according to claim 1, characterized in that: The mass ratio of the curdlan esterified derivative to the collagen is 3-9:1-7.

3. The collagen-based composite nanofiber membrane according to claim 2, characterized in that: The mass ratio of the curdlan esterified derivative to the collagen is 5-8:2-5.

4. The collagen-based composite nanofiber membrane according to claim 1, characterized in that: In the composite nanofiber membrane, the average diameter of the nanofibers is 50 to 500 nm.

5. The collagen-based composite nanofiber membrane according to claim 4, characterized in that: In the composite nanofiber membrane, the average diameter of the nanofibers is 50 to 250 nm.

6. The collagen-based composite nanofiber membrane according to claim 1, characterized in that: In the composite nanofiber membrane, the esterified curdlan derivative includes at least one of acetate curdlan, propionate curdlan, butyrate curdlan, and ester-containing fatty acid curdlan; The collagen includes at least one of type I collagen, type II collagen, type III collagen, type XVII collagen and recombinant humanized collagen.

7. The collagen-based composite nanofiber membrane according to claim 6, characterized in that: The collagen includes type I collagen.

8. A method for preparing a composite nanofiber membrane based on collagen as claimed in any one of claims 1 to 7, characterized in that: The steps include: S1. dissolving the curdlan esterified derivative and the collagen in an organic solvent to obtain an electrospinning solution; S2. The electrospinning solution is formed into the composite nanofiber membrane by electrospinning.

9. The method for preparing the composite nanofiber membrane based on collagen according to claim 8, characterized in that: In S1, the mass volume ratio of the total mass of the curdlan esterified derivative and the collagen to the organic solvent is 1-6%; and the organic solvent includes hexafluoroisopropanol.

10. Use of the composite nanofiber membrane based on collagen as claimed in any one of claims 1 to 7 or the composite nanofiber membrane prepared by the method for preparing the composite nanofiber membrane based on collagen as claimed in any one of claims 8 to 9 in preparing wound dressings or medical implants.

Citation Information

Patent Citations

  • Preparation method of medical fiber wound dressing prepared through composition of natural polysaccharide derivatives and natural polymers

    CN107469127A

  • Cellulose-collagen composite nano-fiber membrane preparation method and wound dressing

    CN109289075A

  • Esterified agarose-cell composite fiber scaffold and preparation method thereof

    CN110393824A

  • Bionic nano fiber material as well as preparation method thereof and application thereof

    CN111793899A

  • Preparation method of composite nanofiber membrane for wound dressing and composite nanofiber membrane

    CN114949325A